2012
DOI: 10.5435/jaaos-20-10-657
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Rotationplasty

Abstract: Rotationplasty is a reconstructive, limb-sparing option for management of lower extremity bone deficiency. This technique involves an intercalary resection, followed by 180° rotation of the distal limb to allow the ankle to function as a knee joint when it is fitted with a modified below-knee prosthesis. Gait analysis and functional outcome studies have reported favorable results with rotationplasty compared with those of above-knee amputation. Moreover, patient satisfaction with rotationplasty is higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 43 publications
0
32
0
2
Order By: Relevance
“…1 The 180° rotation of the distal part of the leg allows for the ankle joint to be used as a functional knee joint when fitted with an appropriately modified below-knee prosthesis. 2 A conventional rotationplasty prosthesis typically consists of a leather thigh cuff and straps, a cast resin socket holding the rotated foot, metal hinges medially and laterally, a prosthetic tube as lower leg and a carbon foot (Figure 1). The thigh cuff is used to stabilize the new knee joint.…”
Section: Background and Aimmentioning
confidence: 99%
“…1 The 180° rotation of the distal part of the leg allows for the ankle joint to be used as a functional knee joint when fitted with an appropriately modified below-knee prosthesis. 2 A conventional rotationplasty prosthesis typically consists of a leather thigh cuff and straps, a cast resin socket holding the rotated foot, metal hinges medially and laterally, a prosthetic tube as lower leg and a carbon foot (Figure 1). The thigh cuff is used to stabilize the new knee joint.…”
Section: Background and Aimmentioning
confidence: 99%
“…Modifications have been made to prevent the derotation of rotated segment by de-attaching all muscle tendon units and re-attaching these 180° opposite of the joint and to address different levels of resection of bone, including a tibial rotationplasty [3436]. …”
Section: Technical and Functional Possibilities With Rotationplastiesmentioning
confidence: 99%
“…16 Transient peroneal nerve palsy is also common, and therefore it is essential to note the integrity of the nerve in the operating theater. 13 Other complications include wound necrosis, pseudarthrosis, non-union and rotational malalignment. 15, 17 …”
Section: Complications and Outcomesmentioning
confidence: 99%
“…Oncologic stage, tumor necrosis, and surgical margins have direct effects on oncologic outcomes, but reconstructive methods appear to be equivalent. 13 Gottsauner-Wolf et al 17 reported local recurrence in 70 patients with malignancies around the knee treated with rotationplasty, after surveillance for a mean of 4 years.…”
Section: Complications and Outcomesmentioning
confidence: 99%